A carbon footprint of HVO biopropane. (18th July 2017) - Johnson, Eric
Abstract: Biopropane made by hydrogenating vegetable or animal oil/fat is being commercialized as a biofuel alternative to liquefied petroleum gas (LPG). Its carbon footprint has been calculated from field to tank, using public data for each process in the supply chain, for six main feedstocks: palm oil, palm oil fatty acid distillate, tallow, used cooking oil, rape oil, and soy oil. Scenarios have been applied to the calculations using four main variables: allocation method, i.e., economic or energy; methane capture at the oil mill (or not); application of indirect land‐use change (or not); and classification of the feedstock as a residue (or not). HVO biopropane's carbon footprint varies, depending on the feedstock and the four variables, from as low as 5 g CO2 e/MJ to as high as 102 g. In most cases, this qualifies for government support, i.e., financial credits and biofuel mandates enacted by EU member states under the Renewable Energy Directive. © 2017 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Chemical Industry and John Wiley & Sons, Ltd.